Simulated operating room aerodynamics to improve air quality and prevent surgical site infections. (30th September 2020) - Messina, G; Spataro, G; Tarroni, M; Cevenini, G
Abstract: Background: Proper operating room (OR) ventilation and air filtration are important measures to prevent infection of the surgical site and consequently reduce hospital stay and healthcare costs. In order to identify how changes in the air system can affect air quality, tailor-made researches need to be conducted in ORs. The aim of the study is to verify how a mobile air filtration system can affect the air quality of ORs when placed in different positions. Methods: This is a descriptive study conducted during April and May 2018 in the University Hospital of Siena, Italy. We measured air flows through the vents of both the OR air system and a mobile novel air system unit, which includes a patented crystalline ultraviolet C reactor and an HEPA filter. Using a CAD 3D simulation software (SolidWorks 2017) the air flows interactions were simulated in the replicated OR. Results: The device influenced the original airflows generated by the integrated OR ventilation system. Simulations have shown that when the device is positioned close to the wall with its intake beside the entrance and its outlet towards the operating table, air from outside can enter the room because the air intake from the device prevails over the internal pressure of the OR, increasing contamination. If the device is placed near the OR centre with its suction towards the operating table and its outlet towards the OR entrance, if the door is opened, airflows towards the outside of the room prevail, improving ability to retain outgoing contaminants. Conclusions: The different positioning of mobile devices that generate clean air flows within ORs can have a significant impact on aerodynamics, which can turn can affect critical aspects of the surgical outcome. In order to achieve an effective device placement and orientation, OR-specific environmental measurements should be carried out. Key messages: Movable devices may help boosting the performance of air systems in operating rooms. Every operating room needs a speciﬁc study in order to obtain the best proﬁt.